Diseño, simulacion e implementacion de un controlador retroalimentado por vision para una plataforma Stewart tipo 6-RSS (2017)
The project is based on the design and implementation of two visual feedback controllers for an already built Stewart platform. The first controller consists of tracking an object that moves above the mobile platform; The objective is to place the center of the platform under the moving object without contacting it. The second part of the project deals with the ball and plate system, whose purpose is to control a ball on the platform in different scenarios, to guide the ball along a path, or to keep it fixed on a point in the plane despite the existence of disturbances. To achieve this goal, a parallel PID controller, implemented on a 6RSS Stewart platform, is used with the feedback of a camera that picks up the coordinates of the moving object. In the implementation process, the camera support was designed and built, an ATX power supply was adapted to operate the whole system and some elements of the platform were modified.--Tomado del Formato de Documento de Grado.